Climatic Factors Affecting The Population Dynamics Of Lentil Aphid In Inner Terai Region Of Nepal - Neupane, S; Subedi, S (SAARC Journal of Agriculture, 2020)
Population dynamics of lentil aphid Aphis craccivora (Hemiptera: Aphididae) was assessed in relation with climatic parameters at the research field of National Maize Research Program (NMRP), Rampur, Chitwan during winter season of two consecutive years 2016 to 2018. The experiment was organized in randomized complete block design consisting 20 lentil varieties with three replications. The crop was sown during last week of November in both the years. The daily meteorological parameters like maximum temperature (Tmax), minimum temperature (Tmin), relative humidity (RH) and rainfall (Rf) were recorded at the meteorological station located in NMRP, Rampur, Chitwan and then converted into weekly basis as the standard meteorological week (SMW) with correspondence to weekly population of aphid. The incidence of aphid was started from 2nd SMW of January (2 aphid/plant/10 cm apical twigs) during both experimentation years. Initially the population was low and gradually increased and reached to its peak (49 aphid/plant/10cm apical twigs) on 9th SMW i.e. first week of March with correspondence to weather parameters viz. maximum and minimum temperature (°C), relative humidity (%) and rainfall (mm) were 30.80, 15.34, 67.72 and 0, respectively over the years. The aphid population had significant positive correlation with Tmax (r= 0.94) while the Tmin showed highly significant correlation (r=0.99). The relative humidity (RH) had non significant negative correlation (r= -0.90) and rainfall (Rf) showed non significant negative impact (r= - 0.15) with aphid population. The regression model developed could explain 99% variation in aphid population in different cultivars of lentil. SAARC J. Agri., 17(2): 155-164 (2019)